Potential Health Benefits of Selayar Orange Peel (Citrus Nobilis Loureiro) in Selayar Society Perspective - Ria Qadariah Arief; Ridwan Amiruddin; Citrakesumasari; Syamsiah Russeng; Nurhaedar Jafar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectivity: This study aimed to examine the health benefits of orange peels from the perspective of thegeneral public.Methods: This study involved the Selayar Society in the Batangmatasapo area. The data used seveninformants and literature sources of the health benefit orange peels. Analyze data using Excel Office.Results: This study describes some of the benefits of Selayar orange peel that have used in alternativemedicine on the Selayar Islands in the form of anti-obesity, antipyretic, anti-inflammatory, and as ananalgesic.Conclusion: Selayar orange peel has health benefits in the form of anti-obesity, antipyretic, anti-inflammatory,and analgesic. These results are still in the form of discourse that in the future, will be developed in furtherresearch in the form of an observational study on the content of Selayar orange peel as alternative medicine.